(untitled) (Colección, 2017)
The role of parliaments in foreign policy, in any representative democracy, supposes a crucial dimension to explain the international insertion policy-making process. However, few studies in the Uruguayan academy are concerned with the parliamentary dimension of external relations. In order to fill in this gap, this article studies the Uruguayan parliament performance during the XLVII Legislature (2010-2015), which corresponds to Broad Front’s second government, leaded by José Mujica. For this purpose, as a first step an institutional framework is structured, in which both general considerations regarding parliamentary intervention in foreign policy and particular characteristics of Uruguayan institutions are included. And as a second step, the role of Uruguayan parliament is analyzed during the mentioned Legislature, in the areas of co-decision –regarding treaty approbation, head of Mission designation and troops mobilization- and control, through its capacity of summoning the chancellor.